Trends and applications in knowledge discovery and data mining : PAKDD 2017 Workshops, MLSDA, BDM, DM-BPM Jeju, South Korea, May 23, 2017, Revised selected papers /: PAKDD 2017 Workshops, MLSDA, BDM, DM-BPM Jeju, South Korea, May 23, 2017, Revised selected papers. (2017) - Unknown
No abstract available